Service Quality in Higher Education: Expectations and Perceptions of Students - Asim, Ahmed; Kumar, Naresh (Asian Journal of Contemporary Education, 2018)
Quality of services, as judged by students, has become paramount to attract and retain students in the competitive atmosphere of higher education provision in the Maldives. With increasing awareness, students demand wider choices. Postgraduate students were targeted to ascertain their expectations and perceptions about the quality of services at selected higher learning institution (HEI) in the Maldives. Quantitative data was collected using the SERVQUAL instrument. A cross-sectional survey design was employed, and 72 samples were obtained. The data were analyzed using the statistical package SPSS version 23. After application of Pearson correlation tests and multiple regression analysis, the findings revealed that there was a positive but a weak relationship between expectations and perceptions on all the five different dimensions of the SERVQUAL instrument. Interaction effects related to expectations and perceptions between four different groups were tested using MANOVAs. The results were detected only between groups of males and females and in all the other three pairs of groups, null hypotheses were accepted. Implications and suggestions for future research discussed.